(untitled) (Veterinary Science, 2018)
The present review updates the aspect of the genus fungus Aspergillus and the toxicology characteristics the aflatoxins produce. Physical-chemical aspects of the aflatoxins, pathways to the organism and the problems caused by contact and ingestion are briefly described. Moreover, the analysis techniques used to determine the presence of aflatoxin and the preventive measurements that should be applied in the facilities where cereals are processed or handled in order to avoid sanitary problems either in human beings or animals, are mentioned.